(153) some ideas about economic planning in developing countries بعض الأفكار عن التخطيط الاقتصادي في الدول النامية - Johannes Rudolph (the institute of national planning, 2018)
This study aims to show the subject of the " First International Seminar of INP" by discuss some questions that are relevant to economic planning in the developing countries on the one hand. On the other hand, it shows the lawfulness of the process of economic planning and economic development plus how to elaborate an optimal plan of the national economy.